Assessment of the Efficiency of Public Hospitals in Romania - Laura Asandului; Raluca-Elena Caunic; Cotofrei, Paul (My University, 2023)
Considering the high pressure on the healthcare limited resources, mainly on hospitals, determined by the population ageing, and the increased incidence of chronic and infectious diseases, it is essential to both decrease expenditures and provide good quality healthcare. In this paper we focus on the efficiency of Romanian public hospitals. Our research goals are to identify and examine the inefficient public hospitals in Romania; to determine sources of inefficiency in Romanian public hospitals; to describe a potential reduction in all inputs on average to rationalize hospital resources; and recommend that hospital management be improved. We propose an approach that contains preliminary data analyses to obtain homogeneous distributions, then we use Data Envelopment Analysis to estimate the technical efficiency scores for the hospitals in the sample. The results showed that more than half of the examined small hospitals were technically inefficient and that they could have produced a larger number of discharges and consequently an increased number of inpatient days. Possible reductions in inputs were also indicated. These results suggest ways of improving hospital management and restructuring and reorganizing decisions that can be implemented in the hospital network.
Keywords: hospital efficiency; healthcare; Data Envelopment Analysis